Vitamin D3 serum level in patients with multiple sclerosis - Ardalani, Ghasem Fattahzadeh; Khosravi, Alireza (International Journal of Advances in Medicine, 2017)
Background: The World Health Organization states that the prevalence of MS is increasing. Due to the growth in the number of people with MS, and because this disease involves the working youth community and is a debilitating illness and also there is no exact treatment for it, thus, eliminating the risk factors of this disease through new and cost-effective methods is essential. It has been proven that vitamin D3 performs an active role in the immune system. The role of vitamin D on the immune system is to increase phagocytic monocytes and to reduce secretion of TNF-α, IL-12 and PGE2 by monocytes. Vitamin D3 serum Levels in MS patients have had conflicting results in different studies. The Purpose of this study was to compare serum levels of vitamin D3 in patients with MS and healthy subjects, and also to examine the relationship between vitamin D3 serum levels and the severity and the number of attacks in MS patients during a year. Methods: In this case-control study, 60 patients with MS were selected for case group and 60 healthy people, matched to the case group in terms of sex and living conditions, were chosen as the control group. Serum samples were taken for laboratory examination of vitamin D3 serum levels. Then, the collected data was analyzed by SPSS.16. Results: Of samples 25% were male, and the rest of them were female. The mean age of the control group was 20 ± 4 years and that of case group was 19.3 ± 2.8 years. The prevalence of deficiency and inadequate levels of vitamin D3 was higher in MS patients than healthy people in the control group. Deficiency of vitamin D3 was higher among women in both groups. In MS group, prevalence of inadequate levels of vitamin D3 was 35.6% among women, while it was 13.3% among men. But in the control group, prevalence of inadequate levels of vitamin D3 was higher among men (40% versus 13.3%). The incidence of recurrence was 13.3%, 11.1% and 11.1% among MS patients with normal levels of vitamin D3, MS patients with inadequate levels of vitamin D3, and MS patients with deficiency of Vitamin D3, respectively, but the difference between them was not statistically significant. Conclusions: Results showed that the serum levels of vitamin D3 are low in Ardabil province and even lower among women; and particularly in MS patients compared to healthy people. There was no significant relation between the number of attacks per year and serum levels of vitamin D3.